Structural feasibility of incorporating the LVEM-isolated floor in the first story of a two-story steel frame. (15th November 2019) - Xiang, Yang; Koetaka, Yuji
Highlights: Benefits of installing the LVEM-isolated floor in the first story of a two-story frame. The frame lateral stiffness is basically not weakened by the floor-isolation. A 40% reduction in the peak inter-story drift could be obtained via a regular design. The ambient temperature notably influences the performance of the floor-isolation system. Peak of the floor acceleration response spectra is notably mitigated by the floor-isolation. Abstract: We introduce a novel floor-isolation system for mitigating the seismic responses of steel frames. In the system, the floors are connected to steel beams by the laminated visco-elastic material (LVEM). In this paper, we present the feasibility of installing the LVEM-isolated floors in the first story of a two-story steel moment-resisting frame. Firstly, we notice that the floor-isolation decouples the composite behavior between the floors and the beams, thus weakens the stiffness of the beams. Based on a generalized frame model, it is demonstrated that such a reduction in beam stiffness only yields a tiny decrease in the global lateral stiffness of the frame. Subsequently, the dynamic analysis model is established for the frame equipped with the LVEM-isolated floor. The LVEM isolators are simulated by a refined Kelvin-Voigt model, while the entire structure is modeled by a three-degree-of-freedom system. The accuracy of the numerical approach is validated by shaking table tests. Based on the established model, a large-scale numerical computation is conducted using 136 earthquake records. The results demonstrate that the structural displacement responses could be remarkably mitigated by the floor-isolation. In general, the reduction of the peak inter-story drift gets more pronounced when a larger mass-isolation ratio and a softer LVEM isolator are applied. For a regular structural design configuration (e.g., mass-isolation ration ν = 0.7, LVEM isolator stiffness ratio κ = 0.2), a 40% reduction in the peak inter-story drifts could be obtained via the floor-isolation. The ambient temperature notably affects the performance of the floor-isolation system. In many cases, a risen temperature amplifies the benefits of the floor-isolation while a fallen temperature abates such benefits. Meanwhile, the floor-isolation alters the form and the amplitude of the floor acceleration response spectrum (FARS). The peaks of the FARS are significantly mitigated by the LVEM-isolated floors. Quantitatively speaking, we could get a 50% reduction in the peak of FARS from the LVEM-isolated floor system for regular design configurations, say, ν = 0.7, and κ = 0.2.